The Nona Nori Program: Seaweed Based Innovation for Coastal Community Empowerment in Tablolong Village - Ghofar, Muhammad Azizul (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
In Tablolong Village, Kupang, East Nusa Tenggara, the Nona Nori program is a community empowerment project that emphasizes the use of indigenous seaweed resources. It was created in response to industrial difficulties in locating eco-friendly materials and fluctuating seaweed prices that frequently hurt farmers. Through partnerships between businesses, academic institutions, local organizations, and the government, the program combines technology innovation with the development of community capacity. Research, training, and mentorship initiatives including institutional management training, turning seaweed into novel food products, and creating environmentally friendly anti-corrosion coatings from seaweed extracts are some of the implementation strategies. The outcomes include a greater range of seaweed-based products, the formation of new business groups, and improved community skills.  The initiative also supports social welfare by increasing the economic independence of coastal communities and environmental conservation by encouraging sustainable resource usage.  All things considered, Nona Nori is an example of a sustainable business-community collaboration that generates profit, value, and a shared world.